Use Of Geosynthetics In Road Construction - Bayraktar, Oğuzhan Yavuz (Kastamonu Üniversitesi, 2020)
Road and Railway Stabilization is the use of geosynthetic reinforcing elements to strengthen the ground in order to work on very soft and weak ground in the construction of asphalted or unpaved vehicle roads and rail systems. The geosynthetics increase the performance and design life of highways and railway construction structures in applications such as geogrids, roads, railways, airports and other earthworks with poor ground strength. Geosynthetics offera much higher value than traditional road construction products and the fast, simple installation process greatly reduces the construction process. On highways, Geosynthetics are placed on the weak base floor before the geosynthetic granular substrate is placed. Geosynthetics protect the structural integrity of the slab and prevent the granular sub-base material from slipping into the weak substrate. The use of geosynthetics extends the maintenance requirement of the flooring that is built on a weak floor.
Keywords: Engineering; Mühendislik; Asphalt; Geosynthetic; Road Construction; Railway Stabilization; 11. Sustainability